2021
DOI: 10.1088/1742-6596/1772/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Study on Fluid Descends Vertically on Static Fluid Using Moving Particle Semi-Implicit Method

Abstract: The process of fluid descend vertically on static fluid has been studied through experiment and simulation by using Moving Particle Semi-Implicit (MPS) method. MPS has been developed by Koshizuka and Oka (1996). MPS method is a particle method based on the Lagrangian calculation for incompressible medium and does not rely on grid system. This study has been done by doing simulation first then validated by experiment. Water and cooking oil were used in the experiment. This study was carried out to analyze dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
2
1
1
Order By: Relevance
“…Therefore, it is expected that the temperature did not significantly impact the relocation process, which agrees with Hidayati et al (2020). Furthermore, the splash pattern of this study is similar to the results of Hidayati et al (2021). The splash will arise if the fallen liquid has a higher density where the difference in density between the two is big enough.…”
Section: The Pressure Profilessupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, it is expected that the temperature did not significantly impact the relocation process, which agrees with Hidayati et al (2020). Furthermore, the splash pattern of this study is similar to the results of Hidayati et al (2021). The splash will arise if the fallen liquid has a higher density where the difference in density between the two is big enough.…”
Section: The Pressure Profilessupporting
confidence: 83%
“…While there are many studies analyzing melting interactions between the melted core and solid materials during reactor core melting, there is still limited simulation on the relocation of molten fluids. Studies of the relocation process of some liquids were performed by some researchers, such as Li et al (2013) with silicon oil and salt water, Ilham et al (2018) with freshwater, and Hidayati et al (2021) with cooking oil and freshwater. In this study, the liquids of Al, Fe, and Pb are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…The MPS simulation result in Figure 7 shows that the flow time significantly decreases as a function of temperature. The effect of leak hole size was not obtained in this finding, contrary to the simulation by Hidayati et al, which concluded that the hole size significantly affected the required displacement time [15]. However, these results are similar to the results of Gen Li, et al which showed that at high temperatures the melt transfer of ZrO2 and UO2 becomes faster [9].…”
Section: Figure 6 Effect Of Dynamic Viscosity On Corium Flow Timecontrasting
confidence: 56%
“…Salah satu metode yang dapat digunakan untuk menganalisis proses pelelehan freeze plug adalah metode Moving Particle Semiimplicit (MPS). Metode berbasis partikel ini telah digunakan pada penelitian sebelumnya terkait pengaruh penambahan material tembaga dalam freeze plug [8] dan beberapa kasus nuklir lainnya [9][10][11][12].…”
Section: Latar Belakangunclassified